Pengetahuan Perawatan Kaki terhadap Resiko Ulkus Diabetik Pasien Diabetes Melitus (DM) - Mohammad Arifin Noor; Suyanto Suyanto; Dwi Nur Aini (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the relationship between foot care knowledge and the risk of foot ulcers in Diabetes Mellitus (DM) patients. This type of research is quantitative using a cross-sectional design. The results showed that most DM patients had moderate knowledge (68.2%) with an average risk of foot injuries (63.5%). In conclusion, there is no significant relationship between knowledge about foot care and the risk of developing diabetic foot ulcers. Keywords: Knowledge, Foot Care, Diabetic Ulcer Risk